30 Determination of Optimal Harvest Weight for Mangalica Pigs Using a Serial Harvest Approach to Measure Growth Performance and Carcass Characteristics. (28th November 2020) - Reeves, Maegan A; Charlton, Courtney E; Wilkerson, Shannon R; Rehm, John G; Brandebourg, Terry D
Abstract: Mangalica pigs are a popular niche breed given their reputation for superior quality pork. However, growth and carcass parameters for this breed are poorly documented. Our objective was to better characterize optimal harvest weights for the Mangalica breed. To accomplish this, a growth trial was conducted whereby pigs (n = 56) were randomly distributed across stratified harvest weights (50, 57, 68, 82, 93, 102, 127 kg) in a completely randomized design. Pigs were fed standard finisher rations with individual daily feed intakes and weekly body weights recorded for all animals. At 24h postmortem, carcasses were split and ribbed with marbling and loin eye area (LEA) measured at the 10th rib. Primal cuts were fabricated and individually weighed. Fat back was separated from the loin and weighed. As expected, live weight significantly increased across weight class (P < 0.0001). ADG was similar across classes up to 82 kg live weight before steadily declining with increasing weight class (P < 0.0025). Likewise, feed efficiency did not differ between classes until weights heavier than 82 kg (P < 0.03). LEA significantly increased by class up to 82 kg and then plateaued as harvest weight increased further (P < 0.003). Marbling score significantly increased with increasing weight class up to 102 kg where they then plateaued (P < 0.04). Fat back dramatically increased across all weight classes (P < 0.0001) despite negligible increases in LEA or marbling after 102 kg. Primal cut weights for the ham (P < 0.0001), loin (P < 0.0001), Boston butt (P < 0.0001), shoulder (P < 0.0001), and belly (P < 0.0001) all significantly increased with increasing live weight. These data suggest an optimal harvest weight occurs between 82 to 102 kg while offering little objective justification for the current practice of harvesting Mangalica pigs at much heavier live weights.